„Od posłuszeństwa do wolności”. Tradycje antywolnościowe i kultura opresji szkoły - Głowacka-Sobiech, Edyta (Rocznik Pedagogiczny, 2019)
The article seeks to show how school relationships have changed over the centuries. The main focus is on recent times, when so-called ‘school coercion’ was introduced, accompanied by military re- form and the debate on violence and obedience among pupils. Yet oppression remained in schools, despite being opposed by the most prominent educators and thinkers of the period. Church institu- tions also supported the anti-freedom movements in schools. It is against this background that the slogan of the “new upbringing” movement is presented, which was to give a sense of freedom and respect for other people.